How Can Vulnerable Internally Displaced Persons Be Transitioned from Humanitarian Assistance to Social Protection? : Evidence from Iraq - Obi, Chinedu Temple; Phadera, Lokendra; Wai-Poi, Matthew; Leape, Virginia; Fox, Gabrielle (World Bank, Washington, DC, 2022)
Aligning the short-term humanitarian assistance system with the government social protection system as a possible long-term solution for the displaced population is well discussed in the literature. However, there is limited evidence on how this alignment is applied in a real-world setting. Using field-test data, this paper documents the eligibility of the humanitarian Multi-Purpose Cash Assistance beneficiaries for the government’s poverty-targeted cash transfer program in Iraq. It does so by using two possible approaches —a probabilistic pseudo-proxy-means test, which is based on a limited number of overlapping variables between the targeting models of the humanitarian and government support systems and is designed to be applied on the existing database, and a new data collection with complete sets of variables from the targeting models of the two systems. The paper finds that a significant number of households that qualify for the humanitarian Multi-Purpose Cash Assistance program are eligible for the government’s cash transfer program. While the referral accuracy of the pseudo-proxy-means tests model is high, it is likely to leave out some eligible households. In additions to identifying the cross-eligibility with certainty, collecting new data may elicit important insight related to willingness to be referred. The choice between electing to collect new data or relying on the pseudo-proxy-means tests and using existing data comes with important trade-offs and will depend on the capacity, budget, and appetite for the uncertainty of eligibility.